2020
DOI: 10.1186/s13613-020-0636-2
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility, reproducibility and diagnostic usefulness of right ventricular strain by 2-dimensional speckle-tracking echocardiography in ARDS patients: the ARD strain study

Abstract: Background: Right ventricular (RV) function evaluation by echocardiography is key in the management of ICU patients with acute respiratory distress syndrome (ARDS), however, it remains challenging. Quantification of RV deformation by speckle-tracking echocardiography (STE) is a recently available and reproducible technique that provides an integrated analysis of the RV. However, data are scarce regarding its use in critically ill patients. The aim of this study was to assess its feasibility and clinical useful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 21 publications
3
18
1
Order By: Relevance
“…The right ventricular strain has previously been shown to be useful for prognostication of patients with ARDS [5,38]. Inflammation is thought to cause RV overload and damage that resulted in RV failure, which can be assessed by RV-LS [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The right ventricular strain has previously been shown to be useful for prognostication of patients with ARDS [5,38]. Inflammation is thought to cause RV overload and damage that resulted in RV failure, which can be assessed by RV-LS [17].…”
Section: Discussionmentioning
confidence: 99%
“…Global longitudinal strain (GLS) measurement provides direct measurement of myocardial deformation; thus, it is less affected by different loading conditions compared to ejection fraction [4]. Ventricular strain has been shown to be a useful tool for prognostication in patients with acute respiratory distress syndrome (ARDS) [5]. Studies indicate the potential use of ventricular strain assessment for prognostication in patients with COVID-19 [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…One of the major limitation of TAPSE is its large overlap between patients with and without RV dysfunction [31]. Focusing on patients with ARDS, Lemarié et al used the widely accepted cut-off value of TAPSE (TAPSE<17mm) and found no difference in survival [32]. Moreover, TAPSE evaluates only the motion of the tricuspid annulus without taking into account the complete longitudinal contraction (from base to apex) as RV-LSF does.…”
Section: Tapse and 2d-ste Parametersmentioning
confidence: 99%
“…ml.m -2 vs 33[27][28][29][30][31][32][33][34][35] ml.m -2 , p=0.94), RA volume index(19 [16-29] ml.m -2 vs 19[15][16][17][18][19][20][21][22] ml.m -2 ,p=0.85) and AT RVOT (95 [82-145] ms vs 90 [80-120] ms,p=0.72) between the ACP group and the non ACP group. Pulmonary arterial systolic pressure could not be evaluated because more than 70% of the patients had poor quality of the tricuspid regurgitation doppler flow.…”
mentioning
confidence: 99%
“…Speckle tracking echocardiography is not discussed in the present paper, since it has been recently and extensively described [8]. Moreover, since this technique is time-consuming, it may not be feasible in COVID-19 patients in everyday clinical practice.…”
mentioning
confidence: 99%